Characterization of Sepsis and Sepsis-Associated Encephalopathy. (November 2019) - Feng, Qing; Ai, Yu-Hang; Gong, Hua; Wu, Long; Ai, Mei-Lin; Deng, Song-Yun; Huang, Li; Peng, Qian-Yi; Zhang, Li-Na
Background: Sepsis and sepsis-associated encephalopathy (SAE) are common intensive care unit (ICU) diseases; the morbidity and mortality are high. The present study analyzed the sensitivity of different diagnostic criteria of sepsis 1.0 and 3.0, epidemiological characteristics of sepsis and SAE, and explored its risk factors for death, short-term, and long-term prognosis. Methods: The retrospective study included patients in ICU from January 2015 to June 2016. After excluding 58 patients, 175 were assigned to either an SAE or a non-SAE group (patients with sepsis but no encephalopathy). The sensitivity of the diagnostic criteria was compared between sepsis 1.0 and 3.0, respectively. Between-group differences in baseline data, Acute Physiology and Chronic Health Evaluation II score (APACHE II score), Sequential Organ Failure Assessment score (SOFA score), etiological data, biochemical indicators, and 28-day and 180-day mortality rates were analyzed. Survival outcomes and long-term prognosis were observed, and risk factors for death were analyzed through 180-day follow-up. Results: The sensitivity did not differ significantly between the diagnostic criteria of sepsis 1.0 and 3.0 ( P = .286). The 42.3% incidence of SAE presented a significantly high APACHE II and SOFA scores as well as 28-day mortality and 180-day mortality (all P < .001). The incidence of death was 37.1%. The multivariate stepwise regression analysis demonstrated that the risk of death in SAE group was significantly higher than the non-SAE group ( P < .001). Sepsis-associated encephalopathy is a risk factor for sepsis-related death (relative risk [RR] = 2.868; 95% confidence interval: 1.730-4.754; P < .001). Although males showed a significantly high rate of 28-day and 180-day mortality ( P = .035 and .045), it was not an independent risk factor for sepsis-related death ( P = .072). The long-term prognosis of patients with sepsis was poor with decreased quality of life. No significant difference was observed in prognosis between the SAE and non-SAE groups ( P > .05). Conclusion: Both diagnostic criteria cause misdiagnosis, and the sensitivity did not differ significantly. The incidence of SAE was high, and 28-day and 180-day mortality rates were significantly higher than those without SAE. Sepsis-associated encephalopathy is a risk factor for poor outcome. The overall long-term prognosis of patients with sepsis was poor, and the quality of life decreased.